A REALIDADE DA EDUCAÇÃO FÍSICA NOS ANOS INICIAIS: O ANTES E O DEPOIS DA INSERÇÃO DO SUBPROJETO PIBID NA ESCOLA - Welter, Jaqueline; Welter, Renata; Sawitzki, Rosalvo L. (Salão do Conhecimento, 2013)
Resumo